Adjuvant Probiotics of Lactobacillus salivarius subsp. salicinius AP-32, L. johnsonii MH-68, and Bifidobacterium animalis subsp. lactis CP-9 Attenuate Glycemic Levels and Inflammatory Cytokines in Patients With Type 1 Diabetes Mellitus - Wang, Chung-Hsing; Yen, Hung-Rong; Lu, Wen-Li; Ho, Hsieh-Hsun; Lin, Wen-Yang; Kuo, Yi-Wei; Huang, Yen-Yu; Tsai, Shin-Yu; Lin, Hung-Chih (Frontiers in Endocrinology, 2022)
Type 1 diabetes mellitus (T1DM) is characterized by autoimmune destruction of pancreatic β cells. Probiotic strains residing in the gut play essential roles in host immune regulation. In this clinical trial, we evaluated the therapeutic efficacy of probiotics on patients with T1DM to determine a novel and alternative administration mode for T1DM medication. A randomized, double-blind, placebo-controlled trial was performed at China Medical University Hospital. T1DM patients between 6 and 18 years of age were enrolled. 27 patients were administered two capsules containing probiotic strains Lactobacillus salivarius subsp. salicinius AP-32, L. johnsonii MH-68, and Bifidobacterium animalis subsp. lactis CP-9 daily for 6 months, and 29 patients were administered placebo. The variations of fasting blood glucose and HbA1c in these patients were analyzed. In addition, serum levels of inflammatory cytokines and anti-inflammatory cytokine were assessed using enzyme-linked immunosorbent assay. Patients’ stool microbiota were all subjects to next-generation sequencing (NGS) analysis. NGS data showed elevated populations of Bifidobacterium animalis and Lactobacillus salivarius in the gut of patients with TIDM who were taking probiotics. Patients with T1DM who were administered probiotics showed significantly reduced fasting blood glucose levels compared with the pre-intervention levels. The HbA1c levels of the patients also improved after administration of probiotics. The concentrations of IL-8, IL-17, MIP-1β, RANTES, and TNF-α were significantly reduced and were associated with an increased TGF-β1 expression after probiotic intervention. The persistence effect of glycemic control and immunomodulation were observed even 3 months after discontinuation of the probiotics. Here, we found that probiotics attenuated T1DM symptoms by stabilizing glycemic levels and reducing HbA1c levels in patients with T1DM through beneficial regulation of immune cytokines.